STUDY OF THE PARASITIC MODES FOR THE 140 GHZ GYROTRON OSCILLATOR - Mahmood, Aras; Hussen, Sarkawt (Iraqi Journal of Science, 2024)
This work reports on the particular gyrotron (140 GHz) and how to improve its operation through the elimination of the parasitic modes which excite with the operating mode (). A computer code which was previously constructed has been used to find and analyze the characteristics of the gyrotron especially the starting current of the mode excitation. 021TEThe study involves the parasitic modes of the (140 GHz) gyrotron and the methods of their elimination. Two methods were utilized for this purpose. The first one was the anode voltage variation and the other was the external magnetic field variation. For these two methods all the output characteristics of the gyrotron were analyzed and it was found that the second method is more suitable and gives best results.